Systemic testosterone for the treatment of female sexual interest and arousal disorder (FSIAD) in the postmenopause - Laura Ribera Torres; Sònia Anglès-Acedo; Laura López Chardi; Eduard Mension Coll; Camil Castelo-Branco (Taylor & Francis Group, 2024)
Introduction Female sexual interest and arousal disorder (FSIAD) is the most prevalent female sexual dysfunction in the postmenopause.Objective The aim of this review is to provide a summary of the currently available evidence on the use of testosterone in the treatment of FSIAD in postmenopausal women.Methods A narrative review on the topic was performed. Only randomized controlled trials (RCTs) and systematic reviews and meta-analysis were considered. 123 articles were screened, 105 of them assessed for eligibility, and finally 9 were included in qualitative synthesis following the PRISMA declaration.Results Current evidence recommends, with moderate therapeutic benefit, the use of systemic transdermal testosterone within the premenopausal physiological range in postmenopausal women with Hypoactive Sexual Desire Disorder (HSDD), the previous entity for low desire dysfunction, not primarily related to modifiable factors or comorbidities such as relationship or mental health problems. The available evidence is based on studies with heterogeneity on their design (different testosterone doses, routes of administration, testosterone use in combination and alone, sexual instruments of measurement). There is no data indicating severe short-term adverse effects, although long-term safety data is lacking.Conclusions Despite having testosterone as a valuable tool, therapeutic strategies are lacking in the pharmacological field of HSDD/FSIAD. Neuroimaging studies could provide valuable information regarding the sexual desire substrate and suggest the potential application of already approved drugs for women with a good safety profile. The use of validated instruments for HSDD in postmenopausal women, considering the level of distress, is necessary to be able to draw robust conclusions on the evaluated treatments.